Π-Orbital mediated charge transfer channels in a monolayer Gr–NiPc heterointerface unveiled by soft X-ray electron spectroscopies and DFT calculations. Issue 36 (30th August 2022) - Casotto, Andrea; Drera, Giovanni; Perilli, Daniele; Freddi, Sonia; Pagliara, Stefania; Zanotti, Michele; Schio, Luca; Verdini, Alberto; Floreano, Luca; Di Valentin, Cristiana; Sangaletti, Luigi
Abstract : The charge transfer process at a graphene–Ni phthalocyanine interface is investigated by soft X-ray electron spectroscopies and DFT calculations, thus providing fundamental information to develop electronic devices based on this heterojunction. Abstract : With the aim to identify charge transfer channels underlying device development and operation, X-Ray Photoelectron Spectroscopy (XPS), Near-Edge X-Ray Absorption Fine Structure (NEXAFS), and Resonant Photoelectron Spectroscopy (ResPES) have been employed to characterize a novel heterointerface obtained by the controlled evaporation of a Nickel Phthalocyanine (NiPc) monolayer on a single layer of Graphene (Gr) on SiC substrate. Indeed, the Gr–NiPc interface could be a promising candidate for different applications in the field of photonics, optoelectronics, and sensing, provided that clear information on the charge transfer mechanisms at the Gr–NiPc interface can be obtained. The analysis of the spectroscopic data has shown the effective functionalization and the horizontally-flat disposition of the NiPc complexes over the Gr layer. With this geometry, the main intermolecular interaction experienced by the NiPc species is the coupling with the Gr substrate, through π-symmetry orbitals, as revealed by the different behaviour of the valence band photoemission at resonance with the N K-edge and Ni L3 -edge. These results have been supported by the analysis of density functional theory (DFT) calculations, that allowed for a rationalization of the experimental data, showing that charge transfer at the interface occurs from the doubly degenerate eg LUMO orbital, involving mainly N and C (pyrrole ring) p z states, to the holes in the p-doped graphene layer.